2004
DOI: 10.1093/ije/dyh225
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among adolescents in China: 1998 survey findings

Abstract: Background In China, tobacco smoking accounts for approximately 800 000 deaths annually and evidence suggests that tobacco use is rising. To improve tobacco control initiatives directed at youth, we conducted a population-based survey of children ages 11-20 years, both in and out of school. While there have been previous school-based studies on smoking prevalence and smoking-related knowledge, attitudes, and behaviours among adolescents in China, including the Global Youth Tobacco Survey, this survey also desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 21 publications
6
46
1
Order By: Relevance
“…Among Chinese adolescents, it is estimated that 33.3-47.8% of males and 12.8-24.3% of females have initiated smoking (i.e., have smoked at least once), and 15.0-18.30% of males and 1.7-4.0% of females are current smokers [29][30][31][32][33]. Despite substantial and documented tobacco control efforts in China, researchers have found only limited success in preventing or reducing tobacco use among adolescents [28,34].…”
Section: Cigarette Smoking In China: Prevalence and Existing Researchmentioning
confidence: 99%
“…Among Chinese adolescents, it is estimated that 33.3-47.8% of males and 12.8-24.3% of females have initiated smoking (i.e., have smoked at least once), and 15.0-18.30% of males and 1.7-4.0% of females are current smokers [29][30][31][32][33]. Despite substantial and documented tobacco control efforts in China, researchers have found only limited success in preventing or reducing tobacco use among adolescents [28,34].…”
Section: Cigarette Smoking In China: Prevalence and Existing Researchmentioning
confidence: 99%
“…Researchers have found that up to 50% of boys and approximately 10% of adolescent girls in China are now experimenting with cigarette smoking (Yang et al, 2004;Jiang et al, 2006). Furthermore, an increasing trend in smoking and a declining trend in the age of smoking onset are reported in several studies (Yang et al, 1999;Chen et al, 2001;Yang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding media receptivity and its impact on cigarette smoking would be of great significance for tobacco control. In addition to receptivity to pro-tobacco media messages, a number of other factors have also been linked to increased risk of adolescent tobacco use, including smoking behaviors of peers, parents and teachers (Yang et al, 2004;Chen et al, 2006;Wen et al, 2007;Tanski, Stoolmiller, Gerrard, & Sargent, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…If current trends continue, tobacco-caused deaths and diseases such as cancer, heart disease, and premature death will assume greater prominence (S. Niu et al, 1998;G. Yang et al, 2001;G. Yang et al, 2004;G.…”
Section: Prevalencementioning
confidence: 99%
“…Chen, Unger, Cruz, & Johnson, 1999;Chinese Center for Disease Control and Prevention, 2014;Fang, Zheng, & Lin, 2001;Huang & Li, 2005;H. Liu et al, 2012;Unger et al, 2001;Weiss et al, 2008;G. Yang et al, 2004;L.…”
Section: Current Studiesmentioning
confidence: 99%